Aid Under Fire: Development Projects and Civil Conflict - Crost, Benjamin; Felter, Joseph; Johnston, Patrick (American Economic Review, 2014)
We estimate the causal effect of a large development program on conflict in the Philippines through a regression discontinuity design that exploits an arbitrary poverty threshold used to assign eligibility for the program. We find that barely eligible municipalities experienced a large increase in conflict casualties compared to barely ineligible ones. This increase is mostly due to insurgent-initiated incidents in the early stages of program preparation. Our results are consistent with the hypothesis that insurgents try to sabotage the program because its success would weaken their support in the population. (JEL D74, F35, I32, I38, O15, O17, O18, O19)